2014
DOI: 10.1371/journal.pone.0091930
|View full text |Cite|
|
Sign up to set email alerts
|

PmVRP15, a Novel Viral Responsive Protein from the Black Tiger Shrimp, Penaeus monodon, Promoted White Spot Syndrome Virus Replication

Abstract: Suppression subtractive hybridization of Penaeus monodon hemocytes challenged with white spot syndrome virus (WSSV) has identified the viral responsive gene, PmVRP15, as the highest up-regulated gene ever reported in shrimps. Expression analysis by quantitative real time RT-PCR revealed 9410–fold up-regulated level at 48 h post WSSV injection. Tissue distribution analysis showed that PmVRP15 transcript was mainly expressed in the hemocytes of shrimp. The full-length cDNA of PmVRP15 transcript was obtained and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
1
16
2
Order By: Relevance
“…However, both the up-regulation of PmVRP15 in G 8 (P = 0.399) and down-regulation in G 8iA (P = 0.393) were not statistically significant (Fig. 3), contradicting a previous study that showed that PmVRP15 expression in the Thai population was significantly up-regulated in hemocytes at 48 hpi (Vatanavicharn et al, 2014). The disparity between this present study and Vatanavicharn et al (2014) can be explained in two ways.…”
Section: Fig 2 Cumulative Mortality Of P Monodon Fabricius In G 8 Acontrasting
confidence: 98%
See 4 more Smart Citations
“…However, both the up-regulation of PmVRP15 in G 8 (P = 0.399) and down-regulation in G 8iA (P = 0.393) were not statistically significant (Fig. 3), contradicting a previous study that showed that PmVRP15 expression in the Thai population was significantly up-regulated in hemocytes at 48 hpi (Vatanavicharn et al, 2014). The disparity between this present study and Vatanavicharn et al (2014) can be explained in two ways.…”
Section: Fig 2 Cumulative Mortality Of P Monodon Fabricius In G 8 Acontrasting
confidence: 98%
“…Hemolymph was then poured into a microtube and kept on ice. The hemolymph (100 µl) sample was immediately centrifuged at 5,000 x g for 5 minutes at 4°C to separate the hemocyte (pellet) from the hemolymph (Vatanavicharn et al, 2014). The supernatant was discarded whereas the pellet (the hemocyte) was used in RNA isolation.…”
Section: Challenge Experiments and Samplingmentioning
confidence: 99%
See 3 more Smart Citations